2010
DOI: 10.1108/17595901011056631
|View full text |Cite
|
Sign up to set email alerts
|

Post‐disaster housing reconstruction

Abstract: PurposeThis paper aims to report the findings of a study, which analysed the strengths and limitations of two distinct concepts used for post‐disaster housing reconstruction, namely, the donor‐driven and owner‐driven approaches.Design/methodology/approachData were gathered through interviews, questionnaire survey and observations from government, non‐government organizations and the beneficiaries of owner‐driven and donor‐driven programmes in one of the affected districts.FindingsThe paper reveals that benefic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(44 citation statements)
references
References 18 publications
2
41
0
1
Order By: Relevance
“…Other post-disaster related studies such as Ophiyandri et al (2013) have identified community and stakeholder engagement among the CSFs of community-based post-disaster housing reconstruction projects (CPHRP) during the pre-construction in Indonesia. The finding is also consistent with other authors (Ahmed, 2011;Karunasena and Rameezdeen, 2010). Involvement of communities is essential because, they are the first respondents after the disaster.…”
Section: "I Think the Most Decisive Is Our Relationship With The Commsupporting
confidence: 92%
See 1 more Smart Citation
“…Other post-disaster related studies such as Ophiyandri et al (2013) have identified community and stakeholder engagement among the CSFs of community-based post-disaster housing reconstruction projects (CPHRP) during the pre-construction in Indonesia. The finding is also consistent with other authors (Ahmed, 2011;Karunasena and Rameezdeen, 2010). Involvement of communities is essential because, they are the first respondents after the disaster.…”
Section: "I Think the Most Decisive Is Our Relationship With The Commsupporting
confidence: 92%
“…In Angola, the decades of internal strife have resulted in the destruction or deterioration of physical infrastructure, compromising the country's social and economic cohesion, and its regional integration agenda (ADB, 2011). Managing projects in the post-disaster environment requires paramount attention to accelerate the process and improve the human settlement environment (Karunasena and Rameezdeen, 2010;Rouhanizadeh, Kermanshachi and Dhamangaokar, 2019). Consequently, there is need to explore CSFs in PDRPs, as they can have an impact on the successful delivery of reconstruction projects.…”
Section: Introductionmentioning
confidence: 99%
“…The process by which these changes occurred and which provided new paths of development and empowerment in these domains was participation. In line with previous studies, our results showed that participating in various opportunities, even immediately after the incident, provided the chance for people to use their potential, expand their social networks, be involved with their peers and with self-learning, and facilitate their recovery ( 20 , 29 , 30 ). These opportunities prepared them either to activate and resume their past roles and/or to experience new roles.…”
Section: Discussionsupporting
confidence: 92%
“…Even so, relocation projects are distinctive; unlike in-situ reconstruction, there is no preexisting image of the community to catalyze rebuilding. In practice, agency-driven, as opposed to owner-driven, approaches remain the norm [33,34]; thus, we focused on the following list of theorized contributors to livability that may vary between agency-driven projects.…”
Section: Theorized Contributors To Relocation Livabilitymentioning
confidence: 99%